2005
DOI: 10.1111/j.1745-7270.2005.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunodominant Th1-type T cell Epitopes from <italic>Schistosoma japonicum</italic> 28 kDa Glutathione-S-transferase, a Vaccine Candidate

Abstract: Th1-type cytokines produced by the stimulation of Th1-type epitopes derived from defined schistosome-associated antigens are correlated with the development of resistance to the parasite infection. Schistosoma mansoni 28 kDa glutathione-S-transferase (Sm28GST), a major detoxification enzyme, has been recognized as a vaccine candidate and a phase II clinical trial has been carried out. Sheep immunized with recombinant Schistosoma japonicum 28GST (Sj28GST) have shown immune protection against the parasite infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Although this method decreases the possibility of missed epitopes, it needs to synthesize lots of peptides and is very costly and time-consuming (49). In silico prediction has already become a familiar and useful tool for selecting epitopes from immunologically relevant proteins, which can save the expense of synthetic peptides and the working time (50). A previous study demonstrated that the use of the bioinformatics approach to predict B cell epitopes correlated well with the experimental approach (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although this method decreases the possibility of missed epitopes, it needs to synthesize lots of peptides and is very costly and time-consuming (49). In silico prediction has already become a familiar and useful tool for selecting epitopes from immunologically relevant proteins, which can save the expense of synthetic peptides and the working time (50). A previous study demonstrated that the use of the bioinformatics approach to predict B cell epitopes correlated well with the experimental approach (51).…”
Section: Discussionmentioning
confidence: 99%
“…In silico prediction has already become a familiar and useful tool for selecting epitopes from immunological relevant proteins, which can save the expense of synthetic peptides and the working time [44]. Recently, many algorithms have been developed to predict B cell epitopes on a protein sequence based on propensity values of amino acid properties of hydrophilicity, antigenicity, segmental mobility, flexibility, and accessibility [45].…”
Section: Discussionmentioning
confidence: 99%
“…Epitope prediction was carried out as described previously [52][53][54]. Briefly, the amino acid sequences of SjHSP60 (GenBank accession no.…”
Section: Prediction Of Epitopes and Synthesis Of Peptidesmentioning
confidence: 99%